KEPASTIAN HUKUM TERHADAP ORANG ASING YANG DIKENAI TINDAKAN ADMINISTRATIF KEIMIGRASIAN BERDASARKAN PASAL 75 AYAT (1) UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN - Anak Agung Linda Cantika Anak Agung Linda Cantika; Agus Surya Manika (VYAVAHARA DUTA, 2023)
Immigration becomes part of the embodiment in implementing the upholding sovereignty over Indonesian Territory with its duty to maintain order in the life of the nation and state towards prosperous society based on Pancasila and the 1945 Constitution of the Indonesian Republic. Legal development must receive top priority in order to reduce the occurrence of violations and crimes, especially foreigners who are in the territory of Indonesia. Based on this fact, the formulation of the problem in this thesis is how to regulate and legal certainty for foreigners in the territory of the Indonesian Republic who violate Article 75 paragraph (1) of Law Number 6 of 2011 concerning Immigration. The research method used was a normative research method by studying written law from various sources contained in historical theory, philosophy, comparison, structure, composition, scope and subject, articles explanations, formality and the strength of a binding law. This study used a statutory approach, a conceptual approach and a case approach. The data that has been obtained from the results of this study were compiled and analysed qualitatively, then the data was described descriptively The results of this study indicate that the legal certainty for foreigners who are subject to Immigration Administrative Actions based on Article 75 paragraph (1) of Law number 6 of 2011 concerning Immigration refers to the application of clear, permanent, consistent and consequential laws whose implementation cannot be influenced by subjective state of circumstances. The form of immigration administrative action imposed is in accordance to Article 75 paragraph (2) of Law number 6 of 2011 concerning Immigration.